Exploring How Tutors in Higher Education Perceive Their Work and What Direction They Think it Should Take in the Future: A Case Study - Hernández-Amorós , María J.; Martínez-Ruiz, María A. (Journal of University Teaching and Learning Practice, 2024)
University tutoring is a complex area of study involving various factors and agents whose actions are context-dependent. This qualitative study aims to analyse and interpret the experiences of tutors in the course of their work. The participants were 68 tutors, each from one of the seven centres belonging to the University of Alicante (Spain). We carried out conventional and summative content analyses using AQUAD 7 software. The results show that tutors’ feelings are generally positive, though they become disillusioned if students decide to drop tutoring. Nevertheless, the few students that persevere are enough to encourage tutors to reflect on possible improvements to the tutoring programme. Their suggestions reveal their own tutoring style and the need to promote whichever tutoring model best suits the context and the students that construct the tutorial relationship.